Alapvető állami, vagy alapvető tagállami funkciók? következtetések az EUSZ 4. cikk alapján - Tribl Norbert; Jog-erkölcs-kultúra : értékdilemmák és identitások a jogrendszerekben (2019) (Szeged) (2020)
Article 4 of the Treaty on European Union contains provisions which have often been the subject of divergent interpretations both in the practice of the constitutional courts of the Member States and in the case law developed by the Court of Justice of the European Union. Article 4 TEU can be regarded as a quasi-integration clause, but it may even be called a sovereignty clause, which try to reconcile the irreconcilable: the relationship between the constitutional provisions of the Member States and the legal order of the EU. However, the wording of Article 4 TEU (in the absence of a strong political consensus) has also created a number of uncertainties, which interpretative uncertainty coincides with the problems of the Union’;s self-determination: disintegrating or unifying integration? Europe of nations or European nations? Unity in diversity or diversity in unity? These issues often go beyond the scope of constitutional law and presuppose primarily political consensus, which is influenced by a number of factors (ie. social and economic) outside the coordinate system of law. At the same time, one of the most important questions in the process of European integration is realized: who has the highest legal and political power? What is the relationship between sovereignty and the EU as well as the Member States establishing integration and the supranational entity? In the last decade, one of the highlighted areas of European constitutional law (if we accept the existence of this category as independent) is the question of constitutional or national identity, the interpretation of which in the EU is based on Article 4 (2) TEU. The (simplified) central issue of the identity debate within European integration is the relationship between the legal order of the EU and national constitutions: how do EU law and national constitutional regulations relate to each other? Beyond constitutional identity, however, Article 4 (2) TEU contains a second provision that has so far been less at the heart of academic debate, yet it functions as a quasi-domain of interpretation of the first provision. According to this provision, the EU “shall respect their essential State functions, including ensuring the territorial integrity of the State, maintaining law and order and safeguarding national security. In particular, national security remains the sole responsibility of each Member State.” The interpretation of this provision of the TEU (the Union shall respect their essential State functions) is a fundamental issue in defining the relationship between national constitutions and EU law. What do we mean by the essential state functions defined by the TEU? Who is entitled to define the concept of an essential state function? The question is also fundamental because, if we look at this provision restrictively, we must interpret state functions within the framework defined by the EU and we must talk about quasi “Member State functions.” If we look at the provision extensively, it will lead to the supremacy of the classically interpreted state functions to which the EU must adapts. The former interpretation is Euroconform while the latter is Eurosceptic.
Keywords: Társadalomtudományok; Jogtudomány